PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium cepa L.) DI TANAH PMK DENGAN BERBAGAI JENIS PUPUK KANDANG DAN ABU JANJANG KELAPA SAWIT - Ngateman, Ngateman; Sasli, Iwan; Ramadhan, Tris Haris (Agros Journal of Agriculture Science, 2024)
The application of manure and palm oil empty fruit bunch ash can physically, chemically and biologically increase soil fertility. The study aims to determine the role of manures and palm oil empty fruit bunch ash on growth and yield shallots on ultisol soil. The study was conducted in Sanggau Regency, West Kalimantan, from January to April 2023. The study used a factorial randomized block design. The first factor was the treatment of various types of manure with 4 levels (chicken manure, goat manure, cow manure and duck manure). The second factor is the treatment of palm oil empty fruit bunch ash doses with 3 levels (3.5 tons ha-1, 5 tons ha-1, 6.5 tons ha-1). The type of manure treatment plays a role in influencing plant height aged 4 and 5 WAP, plant dry weight, number of tubers per hill and weight of tubers per hill, with the best type being the use of cow manure. The dose of palm oil empty fruit bunch ash plays a role in influencing the number of tubers per clump, with the best dose being 3.5 tons ha-1.